Planned Science and Scientific Discovery in Equatorial Aeronomy - Hysell, D. L. (Frontiers in Astronomy and Space Sciences, 2022)
This paper discusses the relationship between planning and discovery in science using examples drawn from equatorial aeronomy in general and research at the Jicamarca Radio Observatory in particular. The examples reveal a pattern of discoveries taking place despite rather than because of careful planning.